Factores de riesgo y su incidencia en el desarrollo de bronquiolitis en niños de 0 a 2 años de edad en el Recinto San José, Cantón Babahoyo, octubre 2019 – marzo 2020. - Olivo Chimbo, Ingrid Elizabeth (2020)
The present investigation has the objective of determining that the limited control of risk factors has an impact on the development of bronchiolitis in children from 0 to 2 years of age in the San José compound, Babahoyo canton, from October 2019 to March 2020. applied the descriptive, quantitative, field methodology, using the survey of 30 parents of children under two years of age, the results of which showed that two thirds of children diagnosed with bronchiolitis, are less than one year old, male sex, prevailing acute bronchiolitis (53%), although the chronic type is also representative (47%); The main risks associated with the diagnosis of bronchiolitis in infants were premature births, because almost three quarters of children were preterm, and they did not receive exclusive breastfeeding during their first six months of life. In conclusion, it was identified that the main risk factors were prematurity and limitation in exclusive breastfeeding, which were directly associated with bronchiolitis.